2022
DOI: 10.51253/pafmj.v71i6.7536
|View full text |Cite
|
Sign up to set email alerts
|

Factors Leading to Conversion of Laparoscopic Cholecystectomy to Open Cholecystectomy

Abstract: Objective: To evaluate the various factors leading to conversion of laparoscopic cholecystectomy to open cholecystectomy. Study Design: Comparative cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, from May 2020 to Sep 2021. Methodology: This study was conducted on 200 patients who underwent laparoscopic cholecystectomy for any benign pathology during the study period. Data was collected for all the patients who required conversion of surgical proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[75][76][77] Although equipment failure is known to be a preventable cause of conversion, 78 it is still a significant indication for conversion in Africa and other developing settings. 7,25,79,80 This is unlike in developed settings where it was reported mainly in the 1990s and early 2000s. 81,82 Proper training, maintenance of laparoscopic instruments and materials, and proper imaging investigations would serve as solutions to reduce the rate of conversion.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[75][76][77] Although equipment failure is known to be a preventable cause of conversion, 78 it is still a significant indication for conversion in Africa and other developing settings. 7,25,79,80 This is unlike in developed settings where it was reported mainly in the 1990s and early 2000s. 81,82 Proper training, maintenance of laparoscopic instruments and materials, and proper imaging investigations would serve as solutions to reduce the rate of conversion.…”
Section: Discussionmentioning
confidence: 89%
“…Studies from other settings have also reported adhesions and hemorrhage to be a major cause of conversion 75–77 . Although equipment failure is known to be a preventable cause of conversion, 78 it is still a significant indication for conversion in Africa and other developing settings 7,25,79,80 . This is unlike in developed settings where it was reported mainly in the 1990s and early 2000s 81,82 .…”
Section: Discussionmentioning
confidence: 99%